PENGARUH ORIENTASI ETIKA, PENGALAMAN DAN KOMPETENSI AUDITOR INTERNAL TERHADAP SKEPTISISME PROFESIONAL SERTA DAMPAKNYA TERHADAP KUALITAS HASIL AUDIT (Survey Pada Inspektorat Jenderal Kementerian Agama RI) - Yani Kurniasih; Darwanto . (Eqien - Jurnal Ekonomi dan Bisnis, 2018)
The aims of this research to prove and explain the positive influence of ethical orientation, experience and competence on the quality of the audit results either directly or through professional skepticism. Methods of analysis using path analysis with significance level of 0.05 (5%). The population in this research is the auditor who acts as team members in audits at the Inspectorate General of the Ministry of Religious Affairs. The sample used were 103 respondents using cluster random sampling method to the audit teams. The test results on the analysis of the level of substructure 1 revealed that ethical orientation and experience have no positive influence to professional skepticism, while competence has positive influence to professional skepticism. The test results on the analysis of the level of the substructure 2 revealed that ethical orientation, experience, and competence have no positive influence to the quality of the audit results, while professional skepticism has positive influence the quality of the audit results. The test results on the analysis of indirect influence revealed that the ethical orientation and experience have no positive influence to the quality of the audit results through professional skepticism, while competence has positive influence to the quality of the audit results through professional skepticism. Keywords : ethical orientation, experience, competence, professional skepticism, the quality of the audit results.